Students’ Alienation in OnlineLearning: A Phenomenological Study in Sociology Subject - Sarwono Sarwono; Sudarmiani Sudarmiani; Nurhadji Nugraha (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aims to describe and analyze the alienation phenomenon experienced by students in dealing with online learning in sociology subject. This study uses a phenomenological study. The research was conducted at a senior high school in Ponorogo Regency. The technique used to determine the subject in this study is purposive sampling. Data collection techniques using observation, interviews and documentation. Meanwhile, the data analysis technique used is the interactive analysis of Miles and Huberman. The results show that students experience maladjustments in the use of technology that is beyond their control and hinders their creativity. These conditions lead to the phenomenon of alienation. The alienation experienced by students includes alienation from their productive activities, alienation from learning goals, alienation of students from fellow students, and alienation of students of their potential. Manifestations of alienation symptoms experienced by students are lazy, heavy, and do not want to know or are indifferent to the online learning process. As a result, alienation conditions experienced by students affect the powerlessness in learning participation. Thus, learning is not a priority (meaninglessness), their actions not based on the value of usefulness and norms that they already understand (normlessness), isolated (social isolation) from the status carried as a student, and students experience alienation (self-estrangement) with their activities and roles.